2022
DOI: 10.1021/acs.analchem.2c04469
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-Free Oxidation Reactions in a Microwave Plasma Torch-Based Ion/Molecular Reactor: An Approach for Predicting the Atmospheric Oxidation of Pollutants

Abstract: The atmospheric oxidation of chemicals has produced many new unpredicted pollutants. A microwave plasma torch-based ion/molecular reactor (MPTIR) interfacing an online mass spectrometer has been developed for creating and monitoring rapid oxidation reactions. Oxygen in the air is activated by the plasma into highly reactive oxygen radicals, thereby achieving oxidation of thioethers, alcohols, and various environmental pollutants on a millisecond scale without the addition of external oxidants or catalysts (6 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…In our previous work, it was demonstrated that microwave plasma can rapidly catalyze the oxidation of some environmental pollutants with simultaneous ionization of the analyte . PFASFs could be converted to PFSAs online in an ambient MPTI source and detected in the negative ion mode of high-resolution mass spectrometry (Figure a).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous work, it was demonstrated that microwave plasma can rapidly catalyze the oxidation of some environmental pollutants with simultaneous ionization of the analyte . PFASFs could be converted to PFSAs online in an ambient MPTI source and detected in the negative ion mode of high-resolution mass spectrometry (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…Argon was introduced as the working gas through the middle and inner tubes and controlled by a rotameter, which could be adjusted within the range of 500–2000 mL/min (typically 1000 mL/min). The input microwave frequency was 2.45 GHz, and the power could be adjusted from 0 to 200 W. During operation, a bright purple columnar plasma beam was generated between the middle tube and the inner tube . The mass spectrometry inlet ESI source was unloaded to create an open ion transfer inlet.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, plasma‐over‐liquid platforms utilizing liquid absorbents have shown significantly improved yield [9] with applications in nanoparticle synthesis, [10a] in which liquid absorbent acts to sequester and protect products formed in the gas phase. Pollutant oxidation has also been achieved by spraying the sample into a microwave plasma torch [10b] . Additionally, charged microdroplets produced via electrospray have shown remarkable results in both reaction acceleration [11] and preparative scale‐up [12] .…”
Section: Introductionmentioning
confidence: 99%